Are Larger Merger Synergies Bad News for Consumers? Endogenous Post‐Merger Internal Organization1. (29th March 2019) - Brito, Duarte; Catalão‐Lopes, Margarida
Abstract: In this paper, we endogenize the post‐merger internal organization of firms, considering two alternative structures: multidivisional, in which separate divisions are kept, and traditional, with cost synergies. We analyze when each structure occurs in equilibrium and how it affects welfare. We show that higher synergies do not necessarily lead to higher consumer surplus: firms can opt for a merger type that does not increase consumer surplus as much as the one that would occur with lower synergies. This highlights the importance of antitrust authorities basing their decisions not just on the magnitude of eventual synergies but also on the post‐merger organizational form.